Implementasi Teknik Scaffolding Untuk Mengembangkan Kecerdasan Kognitif Anak Usia Dini - Amanullah, Akhmad Syah Roni; Wulaningsih, Endang Sri; Sari, Indrayani Nurdiana (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
This study departs from the problem where early childhood experiences delays in cognitive development. The delay in cognitive development is due to the learning model provided by parents or teachers which is still limited to providing advice and